ANALISIS PROSES BERPIKIR KREATIF SISWA SEKOLAH MENENGAH KEJURURUAN (SMK) DALAM PEMECAHAN DAN PENGAJUAN MASALAH MATEMATIKA PADA MATERI PERSAMAAN KUADRAT - Prianggono, Agus (Jurnal Pembelajaran Matematika, 2013)
Abstract : This research was aimed at identifying and describing students creativity level, creative thinking process and the factors which cause the students became not creative in solving and posing mathematics problems. This study was a descriptive qualitative research, which used case study method. Identifying the studentsâ creativity level and the steps of creative thinking were conducted by problem-solving and problem-posing tasks (TPPM). The creativity levels divided into three levels, namely creative, less creative and not creative. The creativity criteria were based on the fluency, flexibility and originality. The stages of creative thinking process were refered to creative thinking model developed by Wallas which has some stages. They are preparation, incubation, illumination, and verification. The data analysis was conducted using Miles and Huberman model. At the preparation stage, less creative students were able to gather relevant information to solve the problem. At the incubation stage, less creative and not creative students were need time to recall what they have learned previously. Not creative students tended to stop and did not find any idea to solve the problem. At the illumination stage, less creative students were able to find ideas, but only give a single solution and did not give another solution. At the verification stage, less creative students and not creative students re-checked their work. The factors which cause the students became not creative in solving and posing the problem were: students failed in finding ideas to complete the task, which had never been done before. Students were trapped in using only a way in solving and posing problems. They werenât able to use various ideas in solving and posing the problems.Keywords : creativity, problem-solving, problem-posing, creative thingking processes.